Respostas
respondido por:
6
a₁ = -9
n = 6
r = 7
a₆ = a₁ + (n - 1) * r
a₆ = -9 + (6 - 1) * 7
a₆ = -9 + 5 * 7
a₆ = -9 + 35
a₆ = 26
PA (-9, -2, 5, 12, 19, 26)
Soma dos termos da PA:
S₆ = [(a₁ + a₆) * n] ÷ 2
S₆ = [(-9 + 26) * 6] ÷ 2
S₆ = [17 * 6] ÷ 2
S₆ = 102 ÷ 2
S₆ = 51
Espero ter ajudado. Valeu!
n = 6
r = 7
a₆ = a₁ + (n - 1) * r
a₆ = -9 + (6 - 1) * 7
a₆ = -9 + 5 * 7
a₆ = -9 + 35
a₆ = 26
PA (-9, -2, 5, 12, 19, 26)
Soma dos termos da PA:
S₆ = [(a₁ + a₆) * n] ÷ 2
S₆ = [(-9 + 26) * 6] ÷ 2
S₆ = [17 * 6] ÷ 2
S₆ = 102 ÷ 2
S₆ = 51
Espero ter ajudado. Valeu!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás